Portfolio Optimization using Shariah-Compliant Asset Pricing Model in Indonesia - Qudratullah, Mohammad Farhan; Hanafi, Syafiq Mahmadah; Sunaryati, Sunaryati (JTAM (Jurnal Teori dan Aplikasi Matematika), 2025)
This paper develops portfolio optimization using the Shariah-Compliant Asset Pricing Model (SCAPM) which maximizes the Sharpe ratio by considering investors' prevention of risk. There are four approaches to developing portfolio optimization (SCAPM without interest rates, SCAPM with zakah rate, SCAPM with nominal gross domestic product growth (GDP), and SCAPM with inflation). This is a quantitative study that implements these models in the Islamic capital market in Indonesia, namely Islamic stocks included in the Jakarta Islamic Index (JII) for the period January 2011-December 2018. Based on the results of the Kendall W concordance test, this study found that the four SCAPM optimum portfolios have a very high level of conformity for return, risk, and performance at a 95% confidence level. In terms of the plot and ratio of return and risk, based on the investor's prevention of risk: the optimum portfolio 1 (risk-seeker) and the optimum portfolio 3 (risk-neutral) tend to give the same results and these portfolios were more efficient than the optimum portfolio 2 (risk-averter). This study contributes to the existing literature in the area of mathematics and the Islamic capital market, specifically in terms of the optimal Sharia-compliant portfolio. It is the first study developing, implementing, and testing the optimal portfolio with four approaches SCAPM based on the investors' prevention of risk in Indonesia.